LIMINALITY DALAM PENCIPTAAN MUSIK PROGRAMA - Janeru Kennedy; Awerman Awerman; IGN Wiryawan Budhiana (Bercadik: Jurnal Pengkajian dan Penciptaan Seni, 2017)
ABSTRACT The music entitled “Liminality” is inspired by author’s anxiety toward a phenomenon of liminality between the idealism of classical music (western) and traditional music (eastern) that each of them has the strength on its composition technique and discipline. This musical creation represents the condition of liminality materialized into music composition.            This music composition is composed of three parts of orchestra style that consist of traditional idioms conveyed through the conventional method of western music. Pra Liminal describes a self-identity (tradition). Liminal describes ambiguity, and then Post Liminal is the achievement of a new identity that does not eliminate old identity. Keywords: Liminality, Pra Liminal, Liminal, Post Liminal, Traditional, Western Music